Comparative study between use of calretinin and synaptophysin immunostaining in diagnosis of Hirschsprung disease - Fakhry, Tamer; Samaka, Rehab M.; Sheir, Mahmoud; Albatanony, Ayman A. (International Surgery Journal, 2019)
Background: Hirschsprung disease (HD) is diagnosed by absence of ganglion cells in rectal biopsy. In some cases, standard methods fail to diagnose agangliosis. The aim of this study is to assess the diagnostic value of immunohistochemistry (IHC) of calretinin and synaptophysin compared to standard methods. Methods: This prospective cross section study was conducted in Menoufia University hospitals, Egypt spanning the period between October 2017 to December 2018. Rectal biopsies of the clinically suspected HD patients stained with calretinin and synaptophysin and their results compared to the standard hematoxylin and eosin (H&E) stained sections. Results: A total of 30 patients aged from 3 days to 2 years with a male to female ratio 11:4 were examined for rectal biopsies. Sections of 9 cases were diagnosed HD. In inadequate specimens, sensitivity and specificity of calretinin and synpatophysin (100%, 80%) and (100%, 85.71%) respectively were superior to the sensitivity (40%) and specificity (14%) of H&E. However, in adequate specimens, results of H&E, calretinin and synaptophysin were the same. Conclusions: Immunohistochemical expression of calretinin and synaptophysin were conclusive, diagnostic and superior to the results of H&E stained section in inadequate. However, in adequate specimens calretinin and synaptophysin were consistent and confirmatory to the results of H&E sections.